The Doping Threshold in Sport Contests: An Auction-based Approach - Daniel Müller (Verein für Socialpolitik, 2010)
We analyze the infuence of the number of competitors, the costs of doping and the distribution of talents on the doping behavior. In an n-player strategic game modelled as an all-pay auction, the players have private information about their talent and the amount of doping. The main finding of the analysis is the existence of a doping threshold. Only athletes with a talent above this threshold dope. The value of the doping threshold and the amount of doping the players take depends on the number of players, the costs of doping and the distribution of talents.
Keywords: C72; D44; D82; 330; Auctions; Contests; Doping